2021
DOI: 10.3892/or.2021.8041
|View full text |Cite
|
Sign up to set email alerts
|

Stomatin‑like protein 2 induces metastasis by regulating the expression of a rate‑limiting enzyme of the hexosamine biosynthetic pathway in pancreatic cancer

Abstract: Stomatin-like protein 2 (SLP-2) is associated with poor prognosis in several types of cancer, including pancreatic cancer (PC); however, the molecular mechanism of its involvement remains elusive. The present study aimed to elucidate the role of this protein in the development of PC. Human PC cell lines AsPC-1 and PANC-1 were transfected by a vector expressing SLP-2 shRNA. Analyses of cell proliferation, migration, invasion, chemosensitivity, and glucose uptake were conducted, while a mouse xenograft model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…The altered glutamine flux profiles into UDP-GlcNAc are consistent with previously proposed differences in TCA cycle flux in the D492 model on account of altered glutamine utilization following EMT (9). The increased metabolic flux observed alongside J o u r n a l P r e -p r o o f enhanced expression of GFPT2 is consistent with a mass action effect and corresponds to GFPT2's role as a biomarker for glucose uptake independent of GLUT1 (55,70). 13 C enrichment from the 5-13 C-glutamine was negligible but suggestive of flux rerouting in the TCA cycle, particularly in D492M compared to D492 and D492HER2.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 87%
See 3 more Smart Citations
“…The altered glutamine flux profiles into UDP-GlcNAc are consistent with previously proposed differences in TCA cycle flux in the D492 model on account of altered glutamine utilization following EMT (9). The increased metabolic flux observed alongside J o u r n a l P r e -p r o o f enhanced expression of GFPT2 is consistent with a mass action effect and corresponds to GFPT2's role as a biomarker for glucose uptake independent of GLUT1 (55,70). 13 C enrichment from the 5-13 C-glutamine was negligible but suggestive of flux rerouting in the TCA cycle, particularly in D492M compared to D492 and D492HER2.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 87%
“…Several studies have focused on the function and regulation of GFPT2 related to its role in modulating O-GlcNAcylation of proteins on account of GFPT2 in producing UDP-GlcNAc (21,22,53). GFPT2 has also been shown to counteract oxidative stress (51,69,70), although the mechanism behind that remains elusive. Our results demonstrate that GFPT2 affects protein O-GlcNAcylation, regulates the EMT program, and impacts cellular growth and invasion in a cellular subtype-specific manner in breast epithelial cells, which are consistent with the literature mentioned above.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Stomatin-like protein 2 (STOML2 or SLP2) was primarily identi ed as a protein located in the mitochondrial inner membrane, maintaining the stability of mitochondria (8,9). Previous studies suggested that STOML2 promoted the progression of multiple malignant tumors including liver cancer (10), head and neck squamous cell carcinoma (11), ovarian cancer (12), colorectal cancer (13), and even pancreatic cancer (14). However, the relevant study in pancreatic cancer carried out by Chao et al only demonstrated the relevance of STOML2 and pancreatic cancer patients' prognosis, lacking the support of high-level clinical data such as tissue microarrays.…”
Section: Introductionmentioning
confidence: 99%